2022
DOI: 10.1029/2022je007422
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Model for Pickup Ion Formation at the Moon

Abstract: The lunar exosphere is an ensemble of multiple overlapping, noninteracting neutral distributions that reflect the primary physical processes acting on the lunar surface. While previous observations have detected and constrained the behavior of some species, many others have only circumstantial evidence or theoretical modeling suggesting their presence. Many species are so tenuous as to be unobservable by direct neutral sampling, yet in comparison, measurements in their ionized form provide a particularly sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 187 publications
0
9
0
Order By: Relevance
“…However, the very low density of solar wind plasma in the lunar wake should highly suppress these charge exchange reactions, casting doubt on charge exchange as a major source of ionization at midnight. Meanwhile, works by Halekas et al (2018) and Poppe et al (2022) have revealed no non-solar-wind ion densities higher than 0.3 and 0.1 cm −3 , respectively, within the sunlit portion of the lunar environment, in disagreement with high ion densities predicted by the model of .…”
Section: Discussionmentioning
confidence: 88%
“…However, the very low density of solar wind plasma in the lunar wake should highly suppress these charge exchange reactions, casting doubt on charge exchange as a major source of ionization at midnight. Meanwhile, works by Halekas et al (2018) and Poppe et al (2022) have revealed no non-solar-wind ion densities higher than 0.3 and 0.1 cm −3 , respectively, within the sunlit portion of the lunar environment, in disagreement with high ion densities predicted by the model of .…”
Section: Discussionmentioning
confidence: 88%
“…The low number densities of this very tenuous atmosphere, particularly of the minority species, and the complexity and multiplicity of the source and loss mechanisms (including thermal release, photon stimulated desorption, electron stimulated desorption, sputtering, micrometeorite impact vaporization, etc.) have resulted in a poor understanding of this system (Wurz et al, 2007;Poppe et al, 2022;Wurz et al, 2022). Figure 9 provides the altitude density profiles of the major species, separately for the atoms and molecules released thermally from the regolith and for the atoms released through sputtering.…”
Section: Monitoring the Moon's Surface-bounded Exospherementioning
confidence: 99%
“…− In-situ measurement of freshly ionized pickup ions, originating from the lunar exosphere neutral species. (Hartle and Killen, 2006;Yokota et al, 2009;Wang et al, 2011;Poppe et al, 2022). At high altitudes above the lunar surface, as those of the Gateway orbit (cf.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to its predecessors, BepiColombo does not include a lander and our understanding of Mercury is thus further strongly connected to remote analysis methods. As it is done for the Moon (Poppe et al., 2022), one important method for investigating Mercury's surface has been the analysis of the exosphere around the planet (Killen et al., 2007), allowing insights into composition and surface processes. It is populated by release of atoms from the surface and here sputtering by ion impacts represents a key driver for some species (Wurz et al., 2022).…”
Section: Introductionmentioning
confidence: 99%